Ulv, hest og drage: Ikonografisk analyse af dyrene i stil II-III - Nielsen, Karen Høilund (Hikuin, 2002)
Wolf, Horse, and Dragon An iconographic analysis of the animals of Styles II-III By Karen Høilund Nielsen The fauna of animal Styles II and III can be identified by species to a certain degree, although not so many of the quadrupeds. Meanwhile the corpus of material is now so large that a systematic analysis should provide some insights into the matter. This systematic analysis is based on the occurrence, on single objects, of combinations of body-elements that are supposed to be relevant to the identification of species. Correspondence analysis is applied to the objects and body-elements and the result presents the general relationship between various types of body-elements, with a frequent tendency to clustering. The material is analysed separately for each of the following regions: Scandinavia, Anglo-Saxon England, and the Continent. A series of other details were also recorded: the number of legs, special head-types, and the relationship with earlier and later styles. The result for Scandinavia was a division of the material in seven sub-groups, probably involving three different species. The old terminology of Styles B, C and D is maintained, although the content may vary. B1 is the classical one-ribbon animal, and B2 to some degree the same except that the body-ribbon is now split in two and may diverge. The feet are in both cases usually fringed, the head looking backwards, and the jaws open. The C1 animal still has a body of two ribbons, and the head looking backwards, but the feet are framed and the jaws closed into a muzzle. The C2 animal is growing more triangular and the head is forwardlooking. From the D1 animal onwards we are back to the one-ribbon bodies, but the limbs are growing longer and thinner as is the body. The head is forward-looking, the jaws look more like a pair of pincers and the feet are becoming more claw-like. The eyes change into an oval (almond shape) rather than the usual roundtype. The body has an almost swan-like shape. The entire expression is now more aggressive. The primary change of D2 is the backwards- looking head and a body wound in different figure-eight loops. D3, finally, has its body in a swan-like fashion, but the body diverges markededly and its aggressive attitude is very significant. In the Anglo-Saxon material only B1 is identifiable. The other animal types seem to a large degree to be developments of the Scandinavian B1 animal. It is, however, possible to see some links with the Scandinavian C2 and D1/D3 creatures. On the Continent, the B1 animal and developments based upon it are predominant. The B1 animals, therefore, seem to be well known in all Style II areas, whereas the other Scandinavian animal types seem to be virtually confined to Scandinavia. Only a few traits in the Anglo-Saxon material may indicate some contact within the wider area of the style. On the Continent no adoptation of the aggressive attitude can be identified, although it does turn up in some of the Insular manuscripts. The study of legs shows that the animals in Scandinavia very rarely are seen with less than the expected two pairs of legs. In both Anglo-Saxon England and on the Continent one pair often goes missing. Additionally it can be claimed that form B1 has its roots in Scandinavian Style I, whereas it is impossible to show that the Anglo-Saxon and Continental B1 animals have their roots in the local Style I. In Scandinavia there is thus a continuous development from Style I to II; there is a development of the style as such, but always in a way that makes it clear that the artisan was well aware of the animal and its species and its anatomy. In respect of both Anglo- Saxon England and the Continent the Style II animal seems not to have any roots in Style I. Most of the Style II animals are variations of the B1 animal, and the artist is not very conscious of the animal’s anatomy let alone its species. This may reflect significant differences in the societies of the respective regions. Consequently, the identification of the animals only seems to be significant in respect of the Scandinavian material. The B1 and B2 animals can be identified as wolves primarily on basis of their teeth and their repeated appearance in set combinations with other animals, which may or may not have the teeth. Furthermore, the wolf is basis of many early Scandinavian names and is linked with the wolf-warriors: the Úlfheðnar. The C1 and C2 animals have muzzles and hoofs and bear a clear resemblance to other, more sculptural animals that are undoubtedly horses. They are less easily related to other sources, although many horses appear in Norse mythology, albeit few of them with any still identifiable function. Finally, the D1, D2 and D3 animals bear no resemblance to real animals. They are aggressive animals with long limbs and a long body. It is suggested that they are dragons or serpents. Such creatures are known from the surviving literature, but their appearance is not clearly documented. The wolf must have been a well-known feature all over Style-II Europe, whereas the horse and the dragon seem to be Scandinavian interlude. The origin of the aggressive attitude is unknown, and it may have occurred earlier in Scandinavia than in Britain. Its explanation, although unknown, could still be common.